The Analysis of Islamic Law About The Differences of Friday Sermon with The Two Azan - Muarif, Yahya Zainul (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2022)
This study aims to find out the Islamic law regarding the difference in the number of azan on Friday sermon. The difference is based on the opinion of the scholars who have a strong basis. The differences of opinion among the scientist, when examined in depth, will not actually be a cause of conflict, let alone divisions; instead, they are an alternative or choice in carrying out religious duties. For example, the scholars' differences regarding the Friday sermon with two call to prayer are part of the wealth of Islamic legal treasures which can be practiced at Friday sermon, both using two call to prayer or one call to prayer is sufficient as a call for Friday sermon. This study used a descriptive qualitative method with a literature study approach. The conclusion of this research is Friday sermon, its an opinion that is superior, namely the opinion that the Friday sermon should be performed with two azan, but there is no need to arrogantly humiliate people who perform Friday sermon with one call to prayer.